A cross-sectional study on knowledge and practice of domestic waste management among the households residing in urban field practice area, GIMS, Kalaburagi - Ori, Kimo; Dhadave, Meenakshi M.; Bavule, Sanjeevakumar (International Journal Of Community Medicine And Public Health, 2025)
Background: Effective domestic waste management is critical for public health and environmental sustainability, particularly in rapidly urbanizing areas. Methods: A community-based cross-sectional study was conducted among 320 households selected by simple random sampling. Data were collected using a pre-tested semi-structured questionnaire and analyzed using descriptive statistics and Chi-square tests. Results: Adequate knowledge and practice regarding domestic waste management were observed in 61.9% and 68.8% of respondents, respectively. Knowledge was significantly associated with education level (p=0.012), occupation (p=0.03), marital status (p=0.031), and type of house (p=0.006). However, these variables did not significantly affect practice levels. Despite high access to collection services, 56% still disposed of waste improperly. Conclusions: While knowledge on domestic waste management is relatively high, it does not consistently translate into good practice. Behaviour change interventions and stronger community engagement are essential.